The emotional and priestly logic of plural marriage - Flake, Kathleen, author; Utah State University Press, publisher (Colorado State University. Libraries, 2010)
Kathleen Flake, associate professor of American religious history at Vanderbilt University examines the logic of those women who thrived, rather than suffered, in early Mormon polygamy, and finds that the marriage covenant granted them priestly rights and independence through the powers of heaven.
October 1, 2009.
Keywords: Polygamy -- Religious aspects -- Mormon Church